Genome-wide profiling identifies a DNA methylation signature that associates with TET2 mutations in diffuse large B-cell lymphoma - Asmar, Fazila (Ferrata Storti Foundation, 2013)
The discovery that the Ten-Eleven Translocation (TET) hydroxylases cause DNA demethylation has fundamentally changed the notion of how DNA methylation is regulated. Clonal analysis of the hematopoetic stem cell compartment suggests that TET2 mutations can be early events in hematologic cancers and recent investigations have shown TET2 mutations in diffuse large B-cell lymphoma. However, the detection rates and the types of TET2 mutations vary, and the relation to global methylation patterns has not been investigated. Here, we show TET2 mutations in 12 of 100 diffuse large B-cell lymphomas with 7% carrying loss-of-function and 5% carrying missense mutations. Genome-wide methylation profiling using 450K Illumina arrays identified 315 differentially methylated genes between TET2 mutated and TET2 wild-type cases. TET2 mutations are primarily associated with hypermethylation within CpG islands (70%; P<0.0001), and at CpG-rich promoters (60%; P<0.0001) of genes involved in hematopoietic differentiation and cellular development. Hypermethylated loci in TET2 mutated samples overlap with the bivalent (H3K27me3/H3K4me3) silencing mark in human embryonic stem cells (P=1.5×10(−30)). Surprisingly, gene expression profiling showed that only 11% of the hypermethylated genes were down-regulated, among which there were several genes previously suggested to be tumor suppressors. A meta-analysis suggested that the 35 hypermethylated and down-regulated genes are associated with the activated B-cell-like type of diffuse large B-cell lymphoma in other studies. In conclusion, our data suggest that TET2 mutations may cause aberrant methylation mainly of genes involved in hematopoietic development, which are silenced but poised for activation in human embryonic stem cells.